2020
DOI: 10.1108/dat-05-2020-0025
|View full text |Cite
|
Sign up to set email alerts
|

Public health participation in alcohol licensing decisions in England: the importance of navigating “contested space”

Abstract: Purpose The purpose of this paper is to examine the role of Public Health in licensing following The Police Reform and Social Responsibility Act of 2011, which added ‘health bodies’ as responsible authorities in licensing; in practice, Directors of Public Health undertook this role in England. Despite this legislation facilitating the inclusion of public health in partnerships around licensing, wide variations in involvement levels by public health professionals persist. Design/methodology/approach This pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The 'supportive' approach that some public health stakeholders discussed in our study was also explored by Somerville et al, 16 who found a split in opinion among licensing and police staff. Some felt that public health should have a supportive, more minor role compared with other responsible authorities (e.g.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The 'supportive' approach that some public health stakeholders discussed in our study was also explored by Somerville et al, 16 who found a split in opinion among licensing and police staff. Some felt that public health should have a supportive, more minor role compared with other responsible authorities (e.g.…”
Section: Discussionmentioning
confidence: 71%
“…32 The licensing system has been described as legitimately rejecting this academic evidence base in favour of 'native wisdom', 28 to the frustration of public health stakeholders who reported that licensing board members were more interested in 'anecdote'. This clash of cultures of evidence was also highlighted by Somerville et al 16 Closer examination of the evidence yields a more nuanced understanding. Most studies of alcohol availability have focused on reduced consumption and related acute harms in the short term, with few studies looking at impacts on the longer-term harms on which some public health stakeholders focused.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…These include, for example, engaging local authority stakeholders on licensing policy or seeking to influence decisions on applications. [9][10][11][12][13][14][15] The absence of a health-focused objective for licensing in England (unlike in Scotland) is seen by many English public health teams (PHTs) as hindering their efforts to influence licensing, 14,16,17 and is often perceived as diminishing the legitimacy of public health stakeholders in relation to other statutory bodies. This also makes it more likely that the admissibility of health evidence will be challenged in licensing decisions, where a case can be made that such data are irrelevant to the other objectives.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even without a public health objective, many PHTs in England have sought to work closely with other licensing stakeholders, such as the police, to try to boost their influence on both decisions and policy. 13,14 In Scotland, however, licensing stakeholders also report difficulties applying the public health objective, especially when objecting to individual applications. 9,18 We are unaware of any comparative studies that have examined how legal or structural differences between these two licensing systems (other than the extra objective in Scotland) might affect public health practices.…”
Section: Introductionmentioning
confidence: 99%